Voluntary wheel-running exercise improvement of anxiety or depressive symptoms in different models of depression - Shen, Haodi; Li, Xuemei; Zhai, Junyao; Zhang, Xin (Frontiers in Behavioral Neuroscience, 2024)
The effects of voluntary wheel-running exercise in different rodent models of depression remain unclear, and further research is needed to fully understand the mechanisms underlying these effects.Therefore, this systematic review aimed to evaluate the currently available findings on whether voluntary wheel-running exercise can alleviate depressive symptoms in five different rodent models of depression. The findings of the comprehensive meta-analysis imply that engaging in voluntary wheel-running exercise has a beneficial effect on alleviating depressive symptoms in rodent models that simulate depression.While further research is needed to fully understand the mechanisms and limitations of this intervention future research should aim to conduct larger. Well-designed studies that use standardized protocols and outcome measures. This would help to reduce heterogeneity between studies and improve the overall quality of the evidence base. Additionally, studies should explore the potential mechanisms of action of voluntary wheel-running exercise in treating depression, such as changes in neurotransmitter levels, neuroplasticity, and inflammation.The results suggest that it may hold promise as an adjunctive therapy for depression.